Characterizing Groundwater Flow in Monitoring Wells by Altering Dissolved Oxygen. Issue 2 (26th May 2016) - Vitale, Sarah A.; Robbins, Gary A.
Abstract: In this study, the dissolved oxygen (DO) alteration method (Chlebica and Robbins 2013) is used to evaluate the patterns of flow into and vertically within shallow screened monitoring wells. The method entails bubbling air into a well, followed by conducting DO profiles with time. Tests were conducted in six standard 2" (5 cm) polyvinyl chloride shallow screened monitoring wells at four test sites in Storrs, Connecticut. Test sites vary in formation permeability, flow patterns, and nearby geographic features influencing flow. The method provides a means for groundwater flow characterization and potentially improved interpretation of contamination sampling results in the absence of detailed three‐dimensional hydrogeologic information. Abstract : Article impact statement : The dissolved oxygen method is advantageous in delineating groundwater flow due to its low cost, accessibility, and ease of detectability.